2013
DOI: 10.1007/s11130-013-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Oat Prevents Obesity and Abdominal Fat Distribution, and Improves Liver Function in Humans

Abstract: Obesity is associated with a great diversity of diseases including non-alcoholic fatty liver disease. Our recent report suggested that oat, rich in beta-glucan, had a metabolic-regulating and liver-protecting effect in an animal model. In this study, we performed a clinical trial to further confirm the effect of oat. Subjects with BMI ≥27 and aged 18-65, were randomly divided into a control (n=18) and an oat-treated (n=16) group, taking a placebo or beta glucan-containing oat cereal, respectively, for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 22 publications
4
67
0
8
Order By: Relevance
“…The consumption of oat reduced the levels of AST and ALT, body weight, BMI, percentage of body fat, and waist-to-hip ratio. However, the anatomic changes were not observed on ultrasound examination [67] .…”
Section: Liver Enzymesmentioning
confidence: 86%
“…The consumption of oat reduced the levels of AST and ALT, body weight, BMI, percentage of body fat, and waist-to-hip ratio. However, the anatomic changes were not observed on ultrasound examination [67] .…”
Section: Liver Enzymesmentioning
confidence: 86%
“…Supplementation of oat cereal containing 3 g of b-glucan for 12 weeks reduced body weight and body fat, compared with a cereal without b-glucan [44]. The addition of oat bran (4 or 8 g b-glucan) to biscuits and juice increased satiety compared with the control meal without b-glucan, but b-glucan added only to biscuits did not produce this effect [42].…”
Section: Recent Findingsmentioning
confidence: 96%
“…Recent studies increasingly point to a satietyenhancing effect of oat products, probably attributable to its b-glucan component [42][43][44]. Supplementation of oat cereal containing 3 g of b-glucan for 12 weeks reduced body weight and body fat, compared with a cereal without b-glucan [44].…”
Section: Recent Findingsmentioning
confidence: 99%
“…As well as the use of legumes, it has been shown that oats, a nutritionally rich cereal, can also prolong life and reduce fat [47]. It provides antioxidant, anti-inflammatory and anti-angiogenic properties, and its consumption introduces a lowcalorie intervention through caloric dilution, as well as lowering lowdensity lipoprotein cholesterol, reducing body fat and risk factors for coronary disease [48][49][50][51][52][53].…”
Section: Mammals E Caenorhabiditis Elegansmentioning
confidence: 99%